Integrated metabolomics and bioactivity analysis of new chrysanthemum cultivar petals: Insights into eye-protecting agents - Yifan Wang; Hedi Zhao; Gangqiang Dong; Dan Yang; Xiaofei Liu; Zhuyin Chen; Yanyan Su; Yan Liu; Jingjing Zhu; Jun Zhang; Jing Zhang; Sha Chen (PLoS ONE, 2026)
Chrysanthemum is a globally significant economical crop. Through broadly targeted metabolomics, 58 polyphenols and 65 xanthophylls were quantitatively and qualitatively assessed in chrysanthemum petals. Carotenoids including β-cryptoxanthin, lutein stearate, lutein distearate, lutein dioleate, and lutein oleate, emerged as the primary compounds in both ligulate and tubular flowers, and their levels remaining relatively high and stable during the second to fifth stages of chrysanthemum flower development. However, the compound content varied across developmental stages and tissues. Additionally, the activity of a novel chrysanthemum cultivar extract was evaluated; at a concentration of 62.5 μg/mL, it exhibited significantly greater anti-apoptotic effects than glutathione ( p < 0.001). Moreover, various concentrations of the chrysanthemum extract demonstrated a clear trend in preventing retinopathy. This study integrated chemical composition analysis with activity evaluation to offer fresh insights into the mechanism underlying the development of eye-protecting agents derived from chrysanthemum flowers.